Inventory of Insect Species and Populations on Arenga pinnata in Pargarutan Dolok Village, East Angkola District, South Tapanuli Regency - Siti, Siti Hardianti Wahyuni; Friska, Meiliana; Handayani, Surya; Nasution, Jumaria; Harahap, Sriwinaty (Program Studi Biologi, Fakultas Teknik, Universitas Samudra, 2025)
Palm plants (Arenga pinnata) are a type of palm plant that has high economic value in Indonesia, including in South Tapanuli Regency. All parts of the palm plant, ranging from sap, fruits, leaves, to stems have various benefits. However, in its cultivation, palm plants often face disturbances from insects, both as pests and as pollinating agents that have an important ecological role. Therefore, this study aims to inventory the types and populations of insects associated with palm plants in order to understand insect diversity and identify potential pests and natural predators. This study was conducted in Pargarutan Dolok Village, East Angkola District, South Tapanuli Regency for eight weeks using the anthracane trap method and direct observation. The results showed that insects of the order Hymenoptera, especially the family Apidae, were the group with the highest number of anthracite traps, at 23 individuals. In total, 65 individual insects were found consisting of 6 orders and 10 families. The insect population during the 1st to 4th week was 40 individuals, while in the 5th to 8th week it was 25 individuals. The role of insects found in palm plants includes pollinators, predators, and polyphages.